Experimental research of the prototype of the rotary-piston engine of the transport hybrid power plant - Mytrofanov, Oleksandr S.; Proskurin, Arkadii Yu.; Poznanskyi, Andrii S.; Митрофанов, Олександр Сергійович; Проскурін, Аркадій Юрійович; Познанський, Андрій Станіславович (My University, 2020)
Abstract. Aim. The purpose of the research is to experimentally determine the operational characteristics of a prototype rotary-piston air engine. Methodology. To determine the operational characteristics of the prototype rotary piston air engine, the method of physical modeling was used. The choice of the research method is primarily due to the design and working process of the air engine. The results obtained make it possible to supplement the mathematical model with empirical dependencies and coefficients to increase its accuracy, as well as to obtain practical recommendations for the operation and maintenance of an air engine of a new design. Results. The results of experimental researches of the prototype of the RPD-4.4/1.75 rotary-piston air engine are presented. Experimental studies were carried out without preheating the air at the inlet to the inlet receiver of the air engine, as well as without adjusting the engine operating modes due to the degree of cylinder filling, that is, the control cam was in the middle (neutral) position. The air pressure in the receiver of the air engine, depending on the established test mode, was 0.4, 0.6, and 0.8 MPa. The rotational speed of the central rotor of the air engine varied within 400...1400 rpm. Experimental dependences of changes in effective indicators (average effective pressure, effective power) and torque of a rotary-piston air engine on rotations for various values of air pressure in the intake receiver are given. The maximum effective power of the air engine at the nominal operating mode at an air pressure in the intake receiver of 0.8 MPa and a speed of 1400 rpm was 2.5 kW, and a torque of 17 N∙m. In this case, the maximum torque and average effective pressure are in the speed range n = 950...1200 rpm. The maximum torque value is 18.2 N∙m and the average effective pressure is 0.18 MPa. The dependences of the change in the temporary air consumption depending on the speed and load of the air engine are obtained. So, for the minimum value of air pressure in the inlet receiver of 0.4 MPa and depending on the load, the value of the temporary air flow is in the range of 25...141 kg/h, while for 0.8 MPa – 55...226 kg/h hour. It was found that when regulating the operating modes of the air engine by changing Ps, its optimal value until a power of 1.4 kW is reached is 0.4 MPa. A further increase in the air engine load requires a gradual increase in Ps. Scientific novelty. On the basis of experimental researches, an assessment of the effective and operational qualities of a prototype of the rotary-piston air engine of a new design was carried out. Practical significance. The operational characteristics of the prototype of the RPD-4.4/1.75 rotary-piston air engine were obtained, and the optimal ranges of variation of the main operational parameters of work were determined, at which the highest efficiency of the air engine was achieved.
Експериментальні дослідження дослідного зразка роторно-поршневого двигуна транспортної гібридної енергетичної установки
Mytrofanov, O. S. Experimental research of the prototype of the rotary-piston engine of the transport hybrid power plant = Експериментальні дослідження дослідного зразка роторно-поршневого двигуна транспортної гібридної енергетичної установки / O. S. Mytrofanov, A. Yu. Proskurin, A. S. Poznanskyi // Shipbuilding & Marine Infrastructure. – 2020. – № 2 (14). – P. 38–45.
Keywords: compressed air; rotary piston air engine; effective indicators; degree of filling of the working cylinder; movement mechanism; transport hybrid power plant; стиснуте повітря; роторно-поршневий пневмодвигун; ефективні показники; ступінь наповнення робочого циліндра; механізм руху; транспортна гібридна енергетична установка